In vivo tracking of phosphoinositides in Drosophila photoreceptors. - Hardie, R.C.; Liu, C.H.; Randall, A.S.; Sengupta, S. (Journal of Cell Science, 2015)
In order to monitor phosphoinositide turnover during phospholipase C (PLC)-mediated Drosophila phototransduction, fluorescently tagged lipid probes were expressed in photoreceptors and imaged both in dissociated cells, and in eyes of intact living flies. Of six probes tested, Tb(R332H) (a mutant of the Tubby protein pleckstrin homology domain) was judged the best reporter for phosphatidylinositol (4,5)-bisphosphate [PtdIns(4,5)P2], and the P4M domain from Legionella SidM for phosphatidylinositol 4-phosphate (PtdIns4P). Using accurately calibrated illumination, we found that only ?50% of PtdIns(4,5)P2 and very little PtdIns4P were depleted by full daylight intensities in wild-type flies, but both were severely depleted by ?100-fold dimmer intensities in mutants lacking Ca(2+)-permeable transient receptor potential (TRP) channels or protein kinase C (PKC). Resynthesis of PtdIns4P (t½ ?12?s) was faster than PtdIns(4,5)P2 (t½ ?40?s), but both were greatly slowed in mutants of DAG kinase (rdgA) or PtdIns transfer protein (rdgB). The results indicate that Ca(2+)- and PKC-dependent inhibition of PLC is required for enabling photoreceptors to maintain phosphoinositide levels despite high rates of hydrolysis by PLC, and suggest that phosphorylation of PtdIns4P to PtdIns(4,5)P2 is the rate-limiting step of the cycle.